Experience of Motherhood in Adolescent Mothers in Socio-Cultural Review - Siti Khuzaiyah; Nina Zuhana; Suparni Suparni (Prodi DIII Kebidanan Blora Poltekkes Kemenkes Semarang, 2021)
Giving birth and raising children brings physical and psychological changes to the mother. Adolescent mothers face the process of giving birth to babies with psychological conditions that may be different from mothers who are mature in age. This study aims to analyze the Motherhood Process of Adolescent Mothers Before Birth and Early Child Care in the Socio-Cultural Review Method. This research use desciptive qualitative approach. The sample in this study were 13 mothers aged 20 years with children aged 12 months and had only 1 child. Data collection by using a form containing open questions. Data analysis was carried out using thematic analysis approach. The results showed that the experiences of teenage mothers during late pregnancy before birth were fear, anxiety, anxiety, worry, and happiness. The expectations of teenage mothers for their children are healthy, intelligent, normal, solih/solihah, and devoted. The experiences of teenage mothers for the first time caring for their children are fear, awkwardness, nervousness, difficulty and happiness. Learning resources for teenage mothers are family, midwives, traditional healers, books and the internet. The conclusion of the study, a teenage mother experienced various psychological conditions. The culture of using traditional birth attendants during the puerperium has a positive impact on a teenage mother. The closeness of a teenage mother with parents and traditional birth attendants greatly influences the smooth process of achieving motherhood. The support of midwives, parents and traditional birth attendants is needed in providing correct information regarding child care, so that teenage mothers can undergo the birth process and child care period comfortably. Keyword: motherhood; teenage mother; pregnancy; birth; parenting